Designing integrated assessment instrument of English subject in elementary school level - Dian Nashrul Munif; Budi Setiawan; Fitri Yuni Haryani (Universitas Sebelas Maret, 2024)
Learning activities have certain goals to be achieved, this process can be measured by carrying out assessments which is a crucial activity in the teaching and learning process. The main purpose of this activity is to see the extent to which students' abilities are able to grasp lessons in each learning activity. Teachers in this case are also required to be able to develop assessment instruments in all subjects, especially English. Teachers should prepare good and efficient assessment instruments for their students because these assessment instruments will measure student learning outcomes. This study tried to develop effective and easy-to-understand assessment instruments which is used as a reference in assessing the process and learning outcomes of students. This study applied research and development by implementing interviews, observations and documentation as data collection, planning design and conducting limited public trial. The instrument was conducted at Al Husna Full-day Islamic School which. This study produced a reference in implementing English assessment at the elementary school level.